Pengaruh Modal Kerja Dan Arus Kas Terhadap Laba Bersih (Studi Kasus Pada PT Jaya Sukses Makmur Sentosa Tbk Periode 2014-2024) - Ani Meryati (Journal of Innovative and Creativity, 2025)
This study aims to analyze the effect of working capital and cash flow on net income at PT Jaya Sukses Makmur Sentosa Tbk during the period 2014-2024. Working capital, which reflects the company's operational efficiency and short-term liquidity, and cash flow, which represents the company's ability to generate and manage cash from various activities, are crucial aspects of the company's operations. Net income, as a key financial performance indicator, is the focus of this study. The data used are secondary data in the form of annual financial reports of PT Jaya Sukses Makmur Sentosa Tbk from 2014 to 2024, which were analyzed using a panel data regression method. The results of the study indicate that working capital has a positive and significant effect on net income. Similarly, cash flow also has a positive and significant effect on net income. Simultaneously, both variables significantly affect net income, with a substantial contribution in explaining the variation in the company's net income. These findings underscore the importance of optimal working capital management and strong cash flow as key pillars in achieving and maintaining company profitability. The results of this study are expected to provide practical implications for the management of PT Jaya Sukses Makmur Sentosa Tbk in making strategic decisions related to financial management.